Person and/or Nature: Review of the Larche’s Criticism of Metropolitan John Zizioulas - Ђаковац, Александар (Sabornost - The Theological Year-book, 2015)
Larche equals person and individual, and there comes his misunderstanding of Zizioulas. He does not understand that person is a word for relation, and that way staying among the borders of classic scholastic thought. In the other hand, he understands the nature to be a realistic different entity in which persons participate. Because, the Fathers that Larche mentions in many places are directly opposite to Larches thought, he is forced to stretch his interpretation, and is forced to come up with contradictory statements, of many which we have shown.